High-frequency Negative Effect Analysis and Countermeasures of Traction Inverter Based on all SiC MOSFET for Rail Transit - Yongjian ZHI; Deyong YANG; Bingquan ZHU; Keliang YUAN; Zifan GAO; Pengfei LI (机车电传动)
After the adoption of SiC device in traction converter for rail transit, the design of traction system will be negatively affected by the high switching speed and high switching frequency of power switch devices. Combined with theoretical analysis and practical measurement, the influences of SiC and IGBT devices on electromagnetic interference, motor end du/dt, over-voltage and motor bearing voltage of traction inverter system were compared. Finally, the corresponding suppression strategies were proposed to meet existing traction system application requirements in view of the negative effects of SiC MOSFET.